Clinical outcomes after salvage external beam radiotherapy combined with interstitial brachytherapy for locally advanced, recurrent endometrial cancer. Issue Volume 7:Issues 1(2023) (24th January 2023) - Waheed, Asmara; Banerjee, Robyn; Meyer, Tyler; Quirk, Sarah; Doll, Corinne; McGeachy, Philip; Phan, Tien; Roumeliotis, Michael; Martell, Kevin
Abstract: Salvage external beam radiation therapy (EBRT) followed by interstitial brachytherapy is commonly used to treat patients with vaginal recurrence of endometrial cancer. The evidence for this is typically limited to case series treating small volumes of disease. For the present study, 12 consecutive patients with locally advanced, biopsy‐proven vaginal recurrence after surgically treated endometrial cancer who received salvage EBRT (45 Gy in 25 daily fractions to microscopic disease and 55–57.5 Gy to gross nodal disease) with magnetic resonance‐guided interstitial brachytherapy (20–21 Gy in 3 fractions over 2 days) were retrospectively reviewed. The median tumor size of recurrent disease on magnetic resonance imaging was 5 (3–6) cm. Three (25%) tumors involved the bladder wall, three (25%) involved the urethra, and four (33%) extended to the pelvic sidewall. Four (25%) patients had gross nodal disease. On follow‐up, no (0%) patient developed local recurrence. One patient (8%) developed nodal recurrence outside of the radiotherapy treatment volume and then distant metastases, and one patient (8%) developed distant metastasis 2.5 years post‐treatment and subsequently died from the disease. No (0%) other deaths were reported. Zero patients (0%) developed grade ≥4 bowel or bladder toxicity. These data support EBRT with interstitial brachytherapy using modern techniques for locally advanced, vaginal recurrences of endometrial cancer. Abstract :